2016
DOI: 10.1007/s00420-016-1151-5
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour work shifts, increased job demands, and elevated blood pressure in professional firefighters

Abstract: Purpose To investigate whether working conditions (number of 24-h shifts, number of calls, sedentary work, job strain, effort–reward imbalance, and physical demands) are associated with elevated blood pressure and hypertension among professional firefighters. Methods A total of 330 (321 males and 9 females) firefighters were chosen for this study among the Southern California firefighters who participated in a work and obesity project. Working conditions were measured with a firefighter-specific occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 48 publications
5
48
0
Order By: Relevance
“…While demands in the line of duty may directly contribute to physical and mental health outcomes by means of witnessing or engaging in violence in order to fulfill duties, other indirect contributions may also have an impact such as 24-hr shifts, night shifts, diet, or proximity to dangerous neighborhoods (Can & Hendy, 2014; Choi, Schnall, & Dobson, 2016).…”
Section: Individual Level Risk and Sources Of Stressorsmentioning
confidence: 99%
“…While demands in the line of duty may directly contribute to physical and mental health outcomes by means of witnessing or engaging in violence in order to fulfill duties, other indirect contributions may also have an impact such as 24-hr shifts, night shifts, diet, or proximity to dangerous neighborhoods (Can & Hendy, 2014; Choi, Schnall, & Dobson, 2016).…”
Section: Individual Level Risk and Sources Of Stressorsmentioning
confidence: 99%
“…A firefighter may be sedentary or even sleeping and, within 2 min, has to be fully geared up (with gear weighing well in excess of 50 pounds), on the truck, and ready for a dire emergency with almost no information about what will be encountered next. As might be expected, there is a high rate of hypertension (Choi, Schnall & Dobson, ) and of PTSD (Kristin, Klimley, Van Hassel, & Stripling, ) among firefighters. Such reactions are buffered by protective factors that include a strong sense of belongingness and social support from co‐workers and family.…”
Section: Introductionmentioning
confidence: 68%
“…The relationship between ERI and job strain has not been extensively examined. Several studies have reported that job strain (Choi, Schnall, & Dobson, 2016; Whitfield et al, 2016) and ERI (Smith et al, 2016) are related to CVD risk in workers. Furthermore, job stress has been shown to be associated with coronary heart disease in a meta-analysis performed in western countries (Kivimaki et al, 2006) and is emerging as an effective measurement to assess the risk of CVD.…”
Section: Discussionmentioning
confidence: 99%